2020
DOI: 10.1002/col.22478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environment color on individual responses in public spaces of shopping malls

Abstract: This study aims to explore the specific impact of a color's hue, saturation, and brightness value on people's evaluation, behavior, and emotions in the public space of existing shopping malls. Following a field investigation, color composition and distribution characteristics in the public spaces of shopping malls are summarized. In the real scenes, the hues of colors are mainly warm colors, with some supplemented by blue. The saturation of the majority colors, which are almost grayish colors, is lower than 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Third, this study used the most frequently used wood‐coloured furniture in small apartments and 21 environmental colours to generate a typical small apartment to ensure the validity of the experiment. This method is consistent with other studies 47,82,83 . However, some studies have found that the contrast between the colour of the decorations and the atmosphere colour in the environment can also cause different visual perceptions 85 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Third, this study used the most frequently used wood‐coloured furniture in small apartments and 21 environmental colours to generate a typical small apartment to ensure the validity of the experiment. This method is consistent with other studies 47,82,83 . However, some studies have found that the contrast between the colour of the decorations and the atmosphere colour in the environment can also cause different visual perceptions 85 .…”
Section: Discussionsupporting
confidence: 91%
“…First, this study performed colour rendering of typical small apartment scenes and obtained 21 colour scenes to study colour preference and HRV arousal. This method allows participants to fully immerse themselves, to experience the effects of colours in a specific environment, and is a method used in many previous studies 47,82,83 . But there are also some studies that use colour patches for the participants to test the impact of colour 56,84 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of experimental environment, most of the studies were carried out in the laboratory where interviewees conducted color evaluation experiments 6,32,33 . Yi et al studied the impact of environmental colors on individual responses in shopping malls, and showed participants photos taken by field surveys in the laboratory to analyze their responses to colors 34 . Some studies are conducted both online and offline to compare the preference differences in different environments 35,36 …”
Section: Related Workmentioning
confidence: 99%